Respon Nyeri pada Neonatus Paska Pengambilan Darah Setelah Dibedong di Ruang Neonatus RSUD Ngudi Waluyo Wlingi - Tri Winarti (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2015)
Newborns in hospitals often have a variety of invasive procedures, so that the baby is experiencing pain. Baby's sense of discomfort and fear which will result from the pain can be observed through the tears. While wrapping the newborn to fit in a blanket (swaddling) can soothe a fussy baby or cry. The purpose of this study was to identify the effect of swaddling on pain response in neonates after venous blood sampling procedures in hospitals Ngudi Waluyo Wlingi. This study was descriptive. Samples taken by accidental sampling technique with a sample of 35 neonates. The results showed that swaddled neonates after venous blood sampling procedure was 80% (28 respondents) pulse between 120-160 times per minute, 100% (35 respondents) respiration between 30-60 times per minute and 51.4% (18 respondents) SaO2 is greater than 92%. Behavioral responses such as shrill and loud cry was 8.4% (24 respondents), stretching in some facial muscles and facial muscles stretching along each was 4.2% (12 respondents), a strong move is 5.95% (17 respondents ), and increased muscle tone face with flexion of the fingers and toes was 7.7% (22 respondents).Use of swaddling post venous blood sampling procedures in neonates can be used as a way of making neonates feel comfortable and calm.